Single-Nucleotide Polymorphism Variations Associated With Specific Genes Putatively Identified Enhanced Genetic Predisposition for 305-Day Milk Yield in the Girolando Crossbreed - da Cruz, Alex Silva; Silva, Danilo Conrado; Minasi, Lysa Bernardes; de Farias Teixeira, Larissa Kamídia; Rodrigues, Flávia Melo; da Silva, Claudio Carlos; do Carmo, Adriana Santana; da Silva, Marcos Vinicius Gualberto Barbosa; Utsunomiya, Yuri Tani; Garcia, José Fernando; da Cruz, Aparecido Divino (Frontiers in Genetics, 2021)
Milk production phenotypes are the main focus of genetic selection in dairy herds, and although there are many genes identified as related to the biology of these traits in pure breeds, little is known about crossbreed animals. This study aimed to identify potential genes associated with the 305-day milk yield in 337 crossbreed Gir × Holstein (Girolando) animals. Milk production records were genotyped for 45,613 single nucleotide polymorphisms (SNPs). This dataset was used for a genome-wide association study (GWAS) using the 305-day milk yield adjusted for the fixed effects of herd, year, linear and quadratic effects of age at calving (in days), and calving factor averaged per animal. Genes within the significant SNPs were retrieved from the Bos Taurus ARS-UCD1.2 assembly (bosTau9) for gene ontology analysis. In summary, the GWAS identified 52 SNPs associated (p-value ≤ 10-4, FDR = 8.77%) with milk production, including NUB1 and SLC24A2, which were previously described as related to milk production traits in cattle. The results suggest that SNPs associated mainly with NUB1 and SLC24A2 could de useful to understand milk production in Girolando and used as predictive markers for selecting genetic predisposition for milk yield in Girolando.